Activity tuning of cobalt ferrite nanoparticles anchored on N-doped reduced graphene oxide as a potential oxygen reduction electrocatalyst by Zn substitution in the spinel matrix - Kashyap, Varchaswal; Singh, Santosh K.; Kurungot, Sreekumar (Chemistry Select, 2017)
Development of highly efficient and durable ORR catalysts by using non-platinum group metals (such as Co, Fe, Mn, and Zn) is a challenging task in the forward path towards the realization of low-cost energy devices in the commercial stream. The present work deals with an effective strategy wherein an efficient Pt-free electrocatalyst for oxygen reduction reaction (ORR) is prepared by stoichiometrically substituting some fraction of Fe with Zn in cobalt ferrite and anchoring these spinel nanoparticles on nitrogen doped reduced graphene oxide (N-rGO). Zn substitution is found to be significantly altering the ratio of Fe2+/Fe3+ in the cobalt ferrite nanocrystal system with a concomitant promotional influence on its electrocatalytic activity towards ORR. The nanoparticle composition with a Co, Fe and Zn molar ratio of 1.0:1.7:0.3, represented by the formula CoFe1.7Zn0.3O4(CFZn(0.3)), supported over N-rGO has shown 10 mV and 20 mV positive shift in the onset and half-wave potentials, respectively, for ORR in 0.1 M KOH in comparison to the nanoparticles of CoFe2O4 supported over N-rGO (CF/N-rGO). The optimum Zn substitution is found to be narrowing down the difference with the state-of-the-art Pt/C for ORR by 100 and 110 mV in terms of the onset and half-wave potentials, respectively. Most significantly, the homemade catalyst is found to be clearly outperforming the Pt catalyst in terms of the limiting current density and electrochemical durability.
Keywords: Carbon Nano-fiber; Cathod Catalyst; CoFe2O4; Evolution; Magnetic-properties; Membrane fuel- Cell; Metal-Air Batteries; N-doped graphene; Nanocrystalline; nanocrystals; oxygen reduction reaction; performance; Platinium; solvothermal synthesis; Zn substituted cobalt ferrite

Air-cathode interface-engineered electrocatalyst for solid-state rechargeable zinc-air batteries - Manna, Narugopal; Singh, Santosh K.; Kurian, Maria; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2022)
Solid-state rechargeable zinc-air batteries (ZABs) are gaining interest as a class of portable clean energy technology due to their advantages such as high theoretical energy density, intrinsic safety, and low cost. It is expected that an appropriately triple-phase boundary (TPB) engineered, bifunctional oxygen reaction (OER and ORR) electrocatalyst at the air- electrode of ZABs can redefine the performance characteristics of these systems. To explore this possibility, an electrode material consisting of manganese- cobalt-based bimetallic spinel oxide (MnCo2O4)-supported nitrogen-doped entangled graphene (MnCo2O4/NEGF) with multiple active sites responsible for facilitating both OER and ORR has been prepared. The porous 3D graphitic support significantly affects the bifunctional oxygen reaction kinetics and helps the system display a remarkable catalytic performance. The air electrode consisting of the MnCo2O4/NEGF catalyst coated over the gas diffusion layer (GDL) ensures the effective TPB, and this feature works in favor of the rechargeable ZAB system under the charging and discharging modes. As an important structural and functional attribute of the electrocatalyst, the porosity and nitrogen doping in the 3D conducting support play a decisive aspect in controlling the surface wettability (hydrophilicity/hydrophobicity) of the air electrode. The fabricated solid-state rechargeable ZAB device with the developed electrode displayed a maximum peak power density of 202 mW cm(-2), which is significantly improved as compared to the one based on the Pt/C + RuO2 standard catalyst pair (124 mW cm(-2)). The solid-state device which displayed an initial charge-discharge voltage gap of only 0.7 V at 10 mA cm(-2) showed only a small increment of 86 mV after 50 h.
Keywords: air-cathode interface; bifunctional oxygen catalyst; N-doped entangled graphene; solid-state zinc-air battery; spinel oxides